Electrified methane steam reforming on a washcoated SiSiC foam for low‐carbon hydrogen production. Issue 1 (7th February 2022) - Zheng, Lei; Ambrosetti, Matteo; Marangoni, Daniele; Beretta, Alessandra; Groppi, Gianpiero; Tronconi, Enrico
Abstract: In view of largely available renewable electricity as a green future resource, here we report the electrification of a Rh/Al2 O3 washcoated SiSiC foam for methane steam reforming (MSR). We show that, thanks to the suitable bulk resistivity of the SiSiC foam, its direct Joule heating up to relevant temperatures is feasible; the interconnected geometry greatly reduces heat and mass transfer limitations, which results in a highly active and energy efficient system for low‐carbon H2 production. The foam‐based electrified MSR (eMSR) system showed almost full methane conversion above 700°C and methane conversions approaching equilibrium were obtained in a range of conditions. Energy efficiency as high as 61% and specific power consumption as low as 2.0 kWh/ N m H 2 3 were measured at 650°C, at gas hourly space velocity (GHSV) of 150, 000 cm 3 /h/gcat . When driven by renewable electricity, the proposed reactor configuration promises a high potential to address the decarbonization challenge in the near‐term future.